Blue steel - Bradbury, Robert N. (Robert North); Wayne, John, 1907-1979; Lone Star Productions (1933-1935); Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1934)
When Sheriff Jake sees a man at the safe and then finds the payroll gone, he trails him. Just as he is about to arrest him, the man saves his life. Still suspicious, he joins up with the man and later they learn that Melgrove, the towns leading citizen, is trying to take over the area's ranches by having his gang stop all incoming supply wagons. With the ranchers about to sell to Melgrove, the two newcomers say they will bring in provisions. --
John Wayne, Eleanor Hunt, George Hayes, Ed Peil, Yakima Canutt, Lafe McKee, George Cleveland, Earl Dwire.
Cinematographer, Archie Stout ; editor, Carl Pierson.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Gold -- Drama; West (U.S.) -- Drama; Western films; Feature films; Internet videos; Streaming video